Sensory and Chemical Characterization of Endemic Lumi-Lumi Fish Crackers (Harpodon Nehereus) as A Local Wisdom Product - Fara Maulida; Safrida Safrida; Muhammad Irfan Febriansyah; Sri Wahyuni Muhsin (Journal of Nutrition Science, 2025)
Lumi-lumi fish (Harpadon nehereus) is an endemic fish commonly found in West Aceh, known for its high protein content and various minerals. Crackers are a food often consumed as a snack, a complement to dishes, or as an appetite stimulant, with a wide variety of consumers ranging from children to adults. However, the content of crackers made from tapioca is known to have a very low protein content of 0.5%. The addition of lumi-lumi fish is expected to increase the protein content of crackers. This study aims to identify the best formulation and analyse the nutritional content of Lumi-lumi fish crackers. The research method is arranged in a one-factorial Completely Randomised Design, which consists of 4 different levels of Lumi-lumi fish concentration treatment (P0: 0%, P2: 15%, P3: 20%, and P4: 25% Lumi-lumi fish)—then identified the expansion power of crackers between treatments. Next, a hedonic method sensory test was conducted to obtain the selected formulation through a scoring test. The chosen products were analysed for nutritional content in comparison to a control group, namely P0 (0% Lumi-lumi fish). Sixty untrained panellists conducted sensory testing. The results showed a significant effect on the cracker expansion power (P = 0.001), with the highest result obtained by treatment P3 at 58.54%. In the scoring test, the selected Lumi-lumi fish crackers were treatment P3. Then based on the results of nutritional content, it was found that the addition of 25% of Lumi-lumi fish meat was able to increase the nutritional content compared to the control treatment (PO), namely the ash content from 0.83 ± 0.39% to 1.36 ± 0.25%, fat content from 0.42 ± 0.08% to 5.81 ± 0.39%, protein content from 7.16 ± 0.55% to 8.58 ± 0.17% and fiber content from 1.47 ± 0.14% increased to 1.81 ± 0.21%. However, there was a decrease in carbohydrates from 90.11 ± 0.59% to 82.44 ± 0.54%. For the analysis of water content, it follows the rules of SNI 01-2713-2009. To produce Lumi-lumi fish crackers with the best organoleptic acceptance, it is recommended to use a concentration of Lumi-lumi fish of 25%.